Gall wasps—inducers and inquilines (Hymenoptera: Cynipidae and Diplolepididae) from Dobrogea Province (South-Eastern of Romania), including new species records for this area - Şchiopu, Ion (Zootaxa, 2025)
This paper summarizes the results of research undertaken by the author in the South-Eastern Region of Romania, between the Danube River and the Black Sea, known as the Province of Dobrogea, during the period 2013–2024. A total of 123 species of gall wasps (106 gall-inducers and 17 inquilines) belonging to 28 genera (23 gall-inducers and 5 inquilines) collected from this area are presented. Among these, the following stand out: 23 species (19 galls-inducers + 4 inquilines) new for the Dobrogea Povince; 13 species (11 gall-inducers + 2 inquilines) new to the fauna of Romania—Aulacidea andriescui Şchiopu, Tataroğlu & Katılmış, 2024, Aulacidea follioti Barbotin, 1972, Aylax minor Hartig, 1840, Iraella ionescui Pujade-Villar & Şchiopu, 2015, Phanacis dobrogicus Şchiopu, Tataroğlu & Katılmış, 2024, Andricus burgundus Giraud, 1859, Andricus legitimus Wiebes-Rijks, 1980, Andricus trotteri Kieffer,1898, Callirhytis rufescens (Mayr, 1882), Cerroneuroterus aggregatus (Wachtl,1880), Cerroneuroterus obtectus (Wachtl,1880), Synergus ruficornis Hartig, 1840, Synergus clandestinus Wiebes-Rijks, 1980; and a new genus record for Romania—Iraella Nieves-Aldrey, 1994. The sexual generation of Callirhytis glandium (Giraud,1859) and asexual generation of Neuroterus politus Hartig, 1840 are reported for the first time in the entomofauna of Romania.